Correcting gene tree by removal and modification - Beretta, Stefano (2019)
Beretta, S., Castelli, M., & Dondi, R. (2015). Correcting gene tree by removal and modification: Tractability and approximability. Journal Of Discrete Algorithms, 33, 115-129. https://doi.org/10.1016/j.jda.2015.03.005